The Multi‐Targeted Effects of Chrysanthemum Herb Extract Against Escherichia coli O157:H7. (17th December 2012) - Kim, Ki‐Suk; Lim, Dong Jin; Yang, Hea Jung; Choi, Eun‐Kyeong; Shin, Min Hee; Ahn, Kwang Seok; Jung, Sang Hoon; Um, Jae Young; Jung, Hee‐Jae; Lee, Jun Hee; Lee, Seok‐Geun; Jung, Sung‐Ki; et al.
Abstract : The Chrysanthemum lavandulifolium extract, which includes chrysoeriol, sudachitin, and acacetin, has excellent antibiotic effects on Escherichia coli O157:H7 ( E. coli O157). A notable point is that the antibiotic targets of the herb extract are similar to the targets of commonly used antibiotic drugs, including bacterial cell wall biosynthesis, bacterial protein synthesis, and bacterial DNA replication and repair. In addition, the herbal antibiotic inhibits the etiological factors that contribute to the pathogenic property. The herbal sample was extracted and fractionated and then inoculated through a disk diffusion method to confirm its antibiotic effect against E. coli O157. Total RNA was isolated from the affected bacterial cells, and its expression level was analyzed through a microarray analysis. To confirm the accuracy of the microarray data, a real‐time PCR was performed. Three active compounds, chrysoeriol, sudachitin, and acacetin, were identified with a high‐performance liquid chromatography‐electrospray ionization/mass spectrometry chromatogram, and the disk diffusion study confirmed that chrysoeriol and sudachitin contribute to the antibiotic properties of the herb extract. The results demonstrate that the multi‐target efficacy of the herbal sample may indicate the potential for the development of more effective and safer drugs that will act as substitutes for existing antibiotics. Copyright © 2012 John Wiley & Sons, Ltd.